Synthetic Graft Compared With Allograft Reconstruction for Extensor Mechanism Disruption in Total Knee Arthroplasty: A Multicenter Cohort Study. Issue 12 (15th June 2019) - Wood, Thomas J.; Leighton, Jennifer; Backstein, David J.; Marsh, Jacquelyn D.; Howard, James L.; McCalden, Richard W.; MacDonald, Steven J.; Lanting, Brent A.
Abstract : Background: Extensor mechanism disruption after total knee arthroplasty is a serious complication leading to notable patient morbidity. The purpose of this study is to compare the outcomes of extensor mechanism allograft with synthetic graft reconstruction. Methods: We retrospectively identified all patients who underwent extensor mechanism reconstruction using either allograft or synthetic graft from two high-volume academic arthroplasty institutions between 2006 and 2017. We collected extensor lag, need for ambulatory aids, and patient-reported outcome measures, as well as the incidence of postoperative complications and revision surgeries. We evaluated cost differences, considering both material cost and the need for revision surgery. Results: We identified 27 cases. A significantly greater postoperative extensor lag was found in the allograft group ( P = 0.05). Graft failure after synthetic reconstruction was zero, with an overall revision surgery rate of 15%. Graft failure was 21%, and the revision surgery rate was 43% after allograft reconstruction. The allograft cost was significantly higher compared with the synthetic graft cost ( P = 0.001). The mean total cost was 4, 733.08 CAD for the synthetic group and 24, 050.40 CAD for the allograft group ( P = 0.17). Discussion: Synthetic reconstruction for extensor mechanism disruption shows benefit in postoperative extensor lag, graft failure, revision surgery, and cost when compared with allograft. Level of Evidence: Level III